Methotrexate-treated ectopic pregnancy: beta human chorionic gonadotropin serum changes as a success predictor using a mathematical model validation. (March 2017) - Kovaleva, Aleksandra; Irishina, Natalia; Pereira, Augusto; Cuesta-Guardiola, Tatiana; Ortiz-Quintana, Luis
Abstract: Background: Surgical rescue of methotrexate-treated ectopic pregnancy is necessary when tubal rupture or medical therapy failure is detected during post-therapeutic monitoring. It is known that an increased beta human chorionic gonadotropin (β-hCG) concentration is the most important factor associated with treatment failure. Therefore, we suggested that relative changes in serum β-hCG could predict a successful result of medical treatment, leading to facilitation of the decision to forgo the prospect of possible surgical rescue. Methods: A retrospective observational study of 115 patients with an ectopic pregnancy who were treated with a single dosage protocol of 50 mg/m 2 of methotrexate injected intramuscularly was performed at Puerta de Hierro University Hospital and Gregorio Marañón University General Hospital. Standard statistical tests were applied in order to evaluate the relative changes in β-hCG concentration between the 1st and the 4th days following methotrexate injection. Results: Methotrexate treatment has a 95% probability to be successful if the relative change of β-hCG from the 1st to the 4th day of monitoring is within the following interval: [−1.02; 0.15]. Moreover, if the values of β-hCG-relative change from 1st to 4th day of monitoring are within [0.54; 1.2], it assures a negative result of treatment with 95% probability. Therefore, the value 0.15 (15%) of β-hCG relative change can be considered a cut-off value for a positive result to treatment. Conclusions: Our data support that negative β-hCG relative changes on the 4th day of treatment likely predict a successful result of methotrexate therapy, with a cut-off point of 0.15. Expectant management should be carried out in these cases if no clinical indications of surgery are presented.